Challenges in particle physics and 3-3-1 models - Long, Hoang Ngoc (Communications in Physics, 2015)
At present,   particle physics faces problems related with disparity in diphoton decay of Higgs boson,  discrepancybetween theory and experiment of about $3.6 \si$ in anomalous magnetic moment of the muon and neutrino physics.Moreover, the existence of   Dark Matter and the Matter-Antimatter Asymmetry are challenges for any physical model.In this review I present some solutions  in the framework  of  the 3-3-1 models. The  simple (by Higgs sector) models contain the hybrid inflationary scenario and the first-order phase transitions, from which  leptogenesis needed for BAUis followed.By these considerations, some bounds on model parameters are derived.